Prevalence of gestational diabetes mellitus using IADPSG and DIPSI criteria: a cross-sectional study - Ruge, Trupti C.; Kanchana, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Considering the magnitude of adverse pregnancy outcomes related to gestational diabetes, the present study was undertaken to find out the prevalence of gestational diabetes mellitus using the international association of diabetes in pregnancy study groups criteria (IADPSG) and diabetes in pregnancy study group India (DIPSI) criteria to ascertain whether the present practice of diagnosing GDM by the guidelines recommended by DIPSI 21 based on WHO criterion of 2-h PG ≥140 mg/dL can still be followed in this study settings or adopt IADPSG recommendation. Methods: This study was done at Antenatal Clinic, department of obstetrics and gynecology, KLES Dr Prabhakar Kore Hospital, Belgaum from January 2013 to December 2013. A total of 225 pregnant women between 24 to 28 weeks gestations were studied. Diagnosis and the prevalence of GDM were assessed by applying both DIPSI and IADPSG criteria. Results: Most of the women (58.11%) were between 22 to 25 years and the mean age was 23.78±3.38 years. Based on the IADPSG criteria, the prevalence of GDM was 19.11% and by applying DIPSI criteria, prevalence of GDM was 16.89%. The difference in diagnostic capability between IADPSG and DIPSI was found to be 2.8% and the kappa statistics showed good strength of agreement between the two tests (p>0.302; Kappa=0.774). Conclusions: It was concluded that, the diagnosis GDM based on DIPSI is as effective as IADPSG criteria. Further, in resource poor countries like India, DIPSI procedure would be used with an advantage of being less costly and without compromising the clinical equipoise.